Advance Materials Series: Advanced Energy Materials. Edited by Ashutosh Tiwari and Sergiy Valyukh. Issue 10 (7th October 2015) - Chen, Xiaobo; Tian, Lihong
<x xml:space="preserve">Abstract</x> Wiley, Hokoben, 2014, hardcover, 616 pp, $ 200.95, € 169.00—ISBN‐978‐1‐118‐68629‐4